BIOLOGI REPRODUKSI IKAN BALOBO (Hyporhamphus quoyi) HASIL TANGKAPAN JARING BALOBO DI PERAIRAN DESA APARA KABUPATEN KEPULAUAN ARU - Juliet J deFretes; Haruna Haruna; Barbara Grace Hutubessy (Universitas Pattimura, 2024)
Garfish is a small pelagic species that has long been used as a raw material for dry fish production from Maluku called balobo dried fish. Many species of Garfish have been exploited but the species Hyporhamphus quoyi has not much been informed. This study aims to understand the reproductive aspects of Garfish consisting of measuring the sex ratio, changes in the gonad maturity stages (GMS) and counting the size of the first size gonad maturity. Located at the waters of Apara village, Aru Archipelago Regency, this study was conducted using a balobo net from November to December 2023. The catches were identified, measured its fork length (FL cm) and dissected to examine its reproductive organ. The Chi-squire heterogeneity test was occupied to measure sex ratio at different sizes. GMS was accessed based on the morphology of testis and ovary. First size maturity was calculated using Spearman-Karber method. The target fish captured by the balobo net consists of the Hemirhamphus far and Hyporhamphus quoyi. The ratio of male and female Hyporhamphus quoyi is unbalanced (c2=8.36; df=1; P=0.0038) but the sex ratio based on the length distribution of fish is not significantly different ( c2=6.92; df=6; P =0.328). Changes in GMS during the observation period indicate the occurrence of spawning in November. Balobo fish reach gonad maturity at FL = 24.9cm for females and FL = 26.8cm for males. Since the optimum size of the fish Hyporhamphus quoyi caught by balobo net is 27cm, this net produced legal sized of fishes.